Micro-structure in the Joint Friction Plane in Friction Welding of Dissimilar Steels. (2016) - Ratković, Nada; Arsić, Dušan; Lazić, Vukić; Nikolić, Ružica R.; Hadzima, Branislav
Abstract: In the friction welding of dissimilar base metals occurs an uneven heating in the outside and inside zones of materials what causes appearance of various structures in the joint zone. Considering that the objective is achieving of the homogeneous welded joint, an imperative is to analyze the microstructure of the realized welded joint. By the microstructure analysis, one can establish the relationship between the friction welding parameters and the structure that appears in each of the joint's characteristic zones. In addition, it is possible to analyze the potential appearance of flaws during the welding process and to discover the causes for their appearance in order to prevent those in the future. This paper presents a review and analysis of microstructures of the characteristic joint zones in the friction plane of the two different steels, the high-speed steel and carbon steel for tempering. The experiment consisted of varying the friction welding parameters (friction pressure and friction time) and monitoring of micro structure in the joint zone and its immediate vicinity, both from the side of the tempering steel and the HS steel, as well as defining the present phases and compounds. The emphasis was set on analysis of the melting and the mixing zones and carbides created during the welding.